(untitled) (CAHIERS MAGELLANES-NS, 2024)
The study aimed to manufacture an aqueous extract of the Pleurotus ostreatus fungus and evaluate its effectiveness against fungi isolated from rotting fruits. The diagnosis of fungal isolates was made by looking at them under a microscope and analyzing their exterior appearance. Aqueous extract was prepared from Pleurotus ostreatus fungus. By cutting Pleurotus ostreatus basidiocarps into slices, After a 24-hour oven drying process at 50 ± 2 °C, they are ground into a fine powder. After soaking ten grams of P.ostreatus powder in distilled water at a ratio of 1:10 (w/v), the mixture was heated for thirty minutes at 60 ± 2 °C. After 30 minutes of room temperature storage with a cover on, strain the boiling mushroom powder. Filtration centrifugation (10,000 × g for 30 min at 4°C) was used to remove suspended residues, and the supernatant was then collected. The study examined the inhibitory effect of the aqueous extract on the isolated fungi. The diameter of the control colony was 30 mm, but when using aqueous extract of Pleurotus ostreatus, it was reduced to 22.5 mm. This indicates that the aqueous extract has an inhibitory effect on the growth of Aspergillus fumigatus fungus. The aqueous extract had the effect of preventing the Aspergillus nidulans fungus from growing. The colony diameter in the control sample was 34.5 mm, but the colony diameter in the sample treated with aqueous extract was 27.5 mm. The efficacy of the aqueous extract against fungus was demonstrated.